Lupus erythematosus tumidus in childhood treated with antimalarials - Aguirre Hernández, Lina Maria; Toro, Ana María; Del Río, Delsy Yurledy; Ruiz, Ana Cristina (CES Medicina, 2018)
Lupus erythematosus tumidus is a rare dermatosis. It is considered a subtype of chronic cutaneous lupus erythematosus of uncertain pathogenesis, favorable prognosis and rare association with systemic lupus erythematosus. Clinically, it manifests as urticarial-like plaques in photo exposed areas, mainly affecting adults, being extremely rare in pediatric age. Herein, we present two cases of six and nine-year-old male patients with clinical and histological cha-racteristics typical of lupus erythematosus tumidus and poor response to first-line treatment (topical, intralesional steroids and topical calcineurin inhibitors); therefore, it was decided to start systemic therapy with antimalarials, obtaining a very good response. DOI: http://dx.doi.org/10.21615/cesmedicina.32.2.7